Silk fibroin-antigenic peptides-YVO4:Eu3+ nanostructured thin films as sensors for hepatitis C - Lima, Lais R. [UNESP]; Moraes, Marli L.; Nigoghossian, Karina [UNESP]; Peres, Maristela F.S. [UNESP]; Ribeiro, Sidney J.L. [UNESP] (Elsevier, 2016)
Nanostructured films prepared by Layer-by-Layer technique and containing silk fibroin, antigenic peptide NS5A-1 derived from hepatitis C virus (HCV) NS5A protein and YVO4:Eu3+ luminescent nanoparticles, were utilized in sensing of hepatitis C. Detection system exploits the biorecognition between the antibody anti-HCV and the antigenic peptide NS5A-1 through changes in luminescence properties. Films deposition was monitored by UV-vis Absorption and Fluorescence Spectroscopy measurements at each bilayer deposited. The Eu3+ luminescence properties were evaluated in the presence of anti-HCV for optical detection of specific antibody and anti-HIV used as negative control. Significant changes in luminescence were observed in the presence of anti-HCV concentrations. A new immunosensor platform is proposed for optical detection of hepatitis C.
Keywords: Antigenic peptide; Europium; Immunosensor; Luminescent nanoparticles; Silk fibroin